Medical mobile technologies - what is needed for a sustainable and scalable implementation on a global scale? - Johan Lundin; Guy Dumont (Taylor & Francis Group, 2017)
Current advances within medical technology show great potential from a global health perspective. Inexpensive, effective solutions to common problems within diagnostics, medical procedures and access to medical information are emerging within almost all fields of medicine. The innovations can benefit health care both in resource-limited and in resource-rich settings. However, there is a big gap between the proof-of-concept stage and implementation. This article will give examples of promising solutions, with special focus on mobile image- and sensor-based diagnostics. We also discuss how technology and frugal innovations could be made sustainable and widely available. Finally, a list of critical factors for success is presented, based on both our own experiences and the literature.